Practical Applications of NMR to Solve Real-World Problems - Brinson, Robert (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Nuclear magnetic resonance spectroscopy (NMR) has developed from primarily a method of academic study into a recognized technology that has advanced measurement capabilities within many different industrial sectors. These sectors include areas such as national security, energy, forensics, life sciences, pharmaceuticals, etc. Despite this diversity, these applications have many shared technical challenges and regulatory burdens, yet interdisciplinary cross-talk is often limited. To facilitate the sharing of knowledge, this Special Issue presents technical articles from four different areas, including the oil industry, nanostructured systems and materials, metabolomics, and biologics. These areas use NMR or magnetic resonance imaging (MRI) technologies that range from low-field relaxometry to magnetic fields as high as 700 MHz. Each article represents a practical application of NMR. A few articles are focused on basic research concepts, which will likely have the cross-cutting effect of advancing multiple disciplinary areas.